2019
DOI: 10.1111/jocs.14088
|View full text |Cite
|
Sign up to set email alerts
|

Predicting postoperative atrial fibrillation after myocardial revascularization without cardiopulmonary bypass: A retrospective cohort study

Abstract: Introduction Considering the threat imposed by postoperative atrial fibrillation (POAF) after coronary artery bypass grafting (CABG) and the potential benefits of off‐pump CABG, the objective of this study was to describe the incidence and identify predictor factors for POAF in patients undergoing CABG without cardiopulmonary bypass (CPB). Methods In this retrospective cohort study, we enrolled patients undergoing CABG without CPB between December 2008 and December 2011. The independent variables evaluated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
(99 reference statements)
0
7
0
Order By: Relevance
“…within the incidence of prior studies [1][2] [3] . Age is one of the most consistent risk factors for postoperative AF in many previous literature [4] [15] , which was also supported by our research.…”
Section: Discussionmentioning
confidence: 99%
“…within the incidence of prior studies [1][2] [3] . Age is one of the most consistent risk factors for postoperative AF in many previous literature [4] [15] , which was also supported by our research.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, higher thyroid hormone level is associated with increased risk for AF and a prolonged total atrial conduction time (TACT). Additionally, thyroid hormone enhanced the effect of angiotensin II in the atrial myocytes, which can induce atrial hypertrophy and cause atrial remodeling, which is an important reason for POAF [Dietrich 2015;Vidotti 2019]. Although the binary logistic regression analysis did not show an independent risk factor of POAF, we still need to pay attention to this situation in the preoperative management of patients.…”
Section: Baseline Charactersmentioning
confidence: 92%
“…The incidence of new‐onset POAF ranged from 20 to 40% of CABG patients (Higgs et al, 2020; Khan et al, 2019). Despite advanced developments in surgical techniques and guidelines for the prevention of new‐onset POAF after CABG surgery, the incidence of new‐onset POAF has not been changed over the years (Vidotti et al, 2019; Yamashita et al, 2019). Previous studies have reported that POAF has a high risk of longer ICU stay, unexpected ICU readmission, increased risk of stroke and higher in‐hospital mortality when compared with those who do not have POAF (Higgs et al, 2020; LaPar et al, 2014; Phan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As POAF is associated with the increased morbidity and mortality, recent studies have reported that advanced age and pre‐existing comorbidities such as atrial fibrillation, renal failure and heart failure significantly increase the risk of POAF after CABG (Dobrev et al, 2019; Farouk et al, 2018; Greenberg et al, 2017; Gudbjartsson et al, 2020). However, these studies were limited to a certain period, such as preoperative or postoperative, during which they identified the comprehensive risk factors (Higgs et al, 2020; Mangi et al, 2019; Vidotti et al, 2019). Additionally, the risk factors identified in previous studies have been primarily focused on Western populations who underwent CABG (Gudbjartsson et al, 2020; Higgs et al, 2020; Khan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation